2022
DOI: 10.1007/s10899-022-10118-6
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic responses during Gambling: the Effect of Outcome Type and Sex in a large community sample of young adults

Abstract: Psychological theories consider autonomic arousal to be a reinforcer for problem gambling. Structural characteristics such as near-misses, which are non-win events that come close to a real win, have been shown to elicit win-like responses while increasing motivation and gambling persistence. This study investigated the autonomic and subjective responses of young adults to different gambling outcomes. This study also investigated sex differences in autonomic and subjective responses to different gambling outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Second, a meaningful appraisal of directional PA changes as “good” or “bad” is impossible if no linkage to gambling behavior (e. g., stakes set) and wins/losses accrued is performed. Evidence suggests that gambling outcomes interfere with distinct PA reactions ( Hultman et al, 2023 , Lole et al, 2012 , Wilkes et al, 2010 ), but our conceptual approach is not suited to disentangle the effects of mandatory breaks and wins or losses close to the break. Hence, future studies should put PA changes in relation to these framework conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Second, a meaningful appraisal of directional PA changes as “good” or “bad” is impossible if no linkage to gambling behavior (e. g., stakes set) and wins/losses accrued is performed. Evidence suggests that gambling outcomes interfere with distinct PA reactions ( Hultman et al, 2023 , Lole et al, 2012 , Wilkes et al, 2010 ), but our conceptual approach is not suited to disentangle the effects of mandatory breaks and wins or losses close to the break. Hence, future studies should put PA changes in relation to these framework conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the study by Hultman et al. ( 40 ), in which authors showed a different effect of two types of near-misses (i.e., before and after payline), we decided to implement only one type of near-miss (i.e., before the payline) that have been specifically associated with higher heart rate deceleration, higher subjective states of motivations, and slightly higher affective responses.…”
Section: Methodsmentioning
confidence: 99%
“…In this view, it would appear that near-misses have been shown to elicit win-like responses, such as increased HR and motivation and persistence in gambling behaviors. Specifically, Hultman et al., ( 40 ) found that two types of near-misses, in which the last winning symbol is one position before or after the pay line, seem to generate different physiological responses in both HRV and SCRs. While near-misses in which the reel stops one position before the pay line are perceived as more pleasant and are associated with increased motivation to play, compared to the other condition in which near-misses are perceived as aversive and demotivating ( 15 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Data were collected during an experimental session at Västmanland County Hospital, Västerås, Sweden. Eligible participants, based on criteria required for the experimental session, were consecutively included until the final sample was reached [for a detailed report on the inclusion procedure, see Hultman et al (2022) ].…”
Section: Methodsmentioning
confidence: 99%